2009
DOI: 10.2140/pjm.2010.244.309
|View full text |Cite
|
Sign up to set email alerts
|

Separation of relatively quasiconvex subgroups

Abstract: We show that if all hyperbolic groups are residually finite, these statements follow: In relatively hyperbolic groups with peripheral structures consisting of finitely generated nilpotent subgroups, relatively quasiconvex subgroups are separable; geometrically finite subgroups of nonuniform lattices in rank one symmetric spaces are separable; Kleinian groups are subgroup separable. We also show that LERF for finite volume hyperbolic 3-manifolds would follow from LERF for closed hyperbolic 3-manifolds. We prove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Manning and Martínez-Pedroza [24] have shown that this definition is equivalent to definition (QC-3) of the present article.…”
Section: Remarkmentioning
confidence: 58%
“…Manning and Martínez-Pedroza [24] have shown that this definition is equivalent to definition (QC-3) of the present article.…”
Section: Remarkmentioning
confidence: 58%
“…Examples of slender LERF groups are polycyclic groups and, in particular, finitely generated nilpotent groups (see Mal 0 cev [13]). The following theorem was conjectured (without the hypothesis of torsion-freeness) in an earlier version of this paper and proved by the third author and Martínez-Pedroza [14].…”
Section: Resultsmentioning
confidence: 75%
“…Theorem 5.1 [14] Suppose that hyperbolic groups are residually finite. Let G be a torsion-free group which is hyperbolic relative to the peripheral system P D fP 1 ; : : : ; P n g. If P i is slender and LERF for each i , then relatively quasi-convex subgroups of G are separable.…”
Section: Resultsmentioning
confidence: 99%
“…Fully quasiconvex subgroups appear in the work of F. Dahmani [14] where it is shown that, under some hypothesis, the combination of relatively hyperbolic groups along fully quasiconvex subgroups is a relatively hyperbolic group.This class of subgroups also appeared in the the work by J. Manning and the author [22] to prove a consequence of the hypothetical absence of non-residually finite hyperbolic groups that was conjectured by I. Agol, D. Groves and J. Manning [1].…”
Section: Sample Applicationsmentioning
confidence: 72%